MWCNTs-ZnO-SiO2 mesoporous nano-hybrid materials for CO2 capture - Jena, Kishore K.; Panda, Amulya Prasad; Verma, Savita; Mani, Ganesh Kumar; Swain, S. K.; Alhassan, Saeed M. (Journal of Alloys and Compounds, 2019)
Carbon nanostructures and metal nanoparticles based nanohybrid materials have been established as one of advantageous materials for various applications. Here, we present hydrothermal and sol-gel process at low temperature for the synthesis of (3-Aminopropyl) triethoxysilane (APTES)-ZnO-multi-walled carbon nanotubes (MWCNTs) mesoporous nanohybrid materials. TEM and XPS measurements show that uniform size and quasi-spherical ZnO nanoparticles were anchored to the surface of the MWCNTs. SEM observation exhibits that the aggregation of ZnO nanoparticles is greatly reduced due to the steric repulsion of grafted organic groups. The maximum CO2 adsorption capacity at 273 K was 1.32 mmol/g for MWCNTs-APTES-ZnO-B nanohybrid. An increase in the density of ZnO nanoparticles on the surface of MWCNTs resulted in a higher affinity towards CO2 at low pressure. This work provides new research directions for making further advances toward practical utilization of MWCNTs-based CO2 adsorbents. (C) 2019 Published by Elsevier B.V.
Keywords: CO2 capture; Mesoporous; MWCNTs; Nanohybrid; TEM; XPS